Thioredoxin-thioredoxin reductase system of Streptomyces clavuligerus: sequences, expression, and organization of the genes. - Cohen, G (1993)
The genes that encode thioredoxin and thioredoxin reductase of Streptomyces clavuligerus were cloned, and their DNA sequences were determined. Previously, we showed that S. clavuligerus possesses a disulfide reductase with broad substrate specificity that biochemically resembles the thioredoxin oxidoreductase system and may play a role in the biosynthesis of beta-lactam antibiotics. It consists consists of two components, a 70-kDa NADPH-dependent flavoprotein disulfide reductase with two identical subunits and a 12-kDa heat-stable protein general disulfide reductant. In this study, we found, by comparative analysis of their predicted amino acid sequences, that the 35-kDa protein is in fact thioredoxin reductase; it shares 48.7% amino acid sequence identity with Escherichia coli thioredoxin reductase, the 12-kDa protein is thioredoxin, and it shares 28 to 56% amino acid sequence identity with other thioredoxins. The streptomycete thioredoxin reductase has the identical cysteine redox-active region--Cys-Ala-Thr-Cys--and essentially the same flavin adenine dinucleotide- and NADPH dinucleotide-binding sites as E. coli thioredoxin reductase and is partially able to accept E. coli thioredoxin as a substrate. The streptomycete thioredoxin has the same cysteine redox-active segment--Trp-Cys-Gly-Pro-Cys--that is present in virtually all eucaryotic and procaryotic thioredoxins. However, in vivo it is unable to donate electrons to E. coli methionine sulfoxide reductase and does not serve as a substrate in vitro for E. coli thioredoxin reductase. The S. clavuligerus thioredoxin (trxA) and thioredoxin reductase (trxB) genes are organized in a cluster. They are transcribed in the same direction and separated by 33 nucleotides. In contrast, the trxA and trxB genes of E. coli, the only other organism in which both genes have been characterized, are physically widely separated.